EFFECT OF PACKAGING OF CHICKEN PARTS WITH MANFACTURED LOCALLY EDIBLE FILMS CONTAIN FEATHER PROTEIN IN SENSORY EVALUATION DURING REFRIGERATED STORAGE - AL- Azzami , Amar A.; AL-Dhanki, ZIAD T. (Diyala Agricultural Sciences Journal, 2020)
This study was conducted in order to test the efficacy of locally produced edible keratin protein extract from chicken broiler chicken feathers in maintaining the basic specifications of chicken carcasses (chest, thigh and drum stick) and stored in 4 Cₒ heat, by slaughtering 35 meat broths with marketing age After the extraction of the pieces, it was distributed to nine treatments in a laboratory experiment consisting of two factors: the first storage period of 0, 7 and 14 days, and the second agent, the keratin packaging. The first three were not stored and were unpackaged and coated with an edible package containing 2.5 g of keratin and coated with (T1, T2 and T3), respectively. The following three treatments werestored for 7 days in a manner similar to the first three treatments (T4, T5 and T6) respectively, and were stored and the last three treatments were filled for 14 days with the same Previous transactions (T7, T8 and T9), respectively. The results of the study showed that the packaging of chicken pieces 2.5 and 5 keratin contributed to maintaining the sensory specifications of meat in the cuttings (chest, thigh and drum stick) stored from 7 to 14 days, and edible casings made of keratin protein had a role in Maintain the sensory specifications of the studied models for their sequentality, reduce the number of microorganisms that lead to chicken meat's parts spoilage.